Chikungunya, a Risk Factor for Guillain-Barré Syndrome. (9th July 2019) - Stegmann-Planchard, Sophie; Gallian, Pierre; Tressières, Benoit; Leparc-Goffart, Isabelle; Lannuzel, Annie; Signaté, Aissatou; Laouénan, Cédric; Cabié, André; Hoen, Bruno
Abstract: In a matched case-control study where 24 cases developed Guillain-Barré syndrome (GBS) during the 2014 chikungunya outbreak in the French West Indies and 72 controls were blood donors during the same period, chikungunya infection was a risk factor for GBS (odds ratio, 8.3; 95% confidence interval, 2.3–29.7; P = .001).